1981
DOI: 10.3382/ps.0600433
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Phosphorus Requirements of Force-Molted Leghorn Hens

Abstract: Two studies were conducted to determine the phosphorus requirements of forcemolted Leghorn hens. In the first study, diets containing .8, .6, or .4% total phosphorus and 4% calcium were fed. In the second study diets with levels of .7, .6, .5, or .4% total phosphorus and 3.8% calcium were fed.Decreasing the phosphorus level improved shell quality as measured by specific gravity and shell thickness. However, egg production and egg weight decreased as phosphorus level decreased. Thus, in these studies a total ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
5

Year Published

1986
1986
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
2
0
5
Order By: Relevance
“…However, fewer studies have investigated AP requirement of molted laying hens (Holder, 1981;Said et al, 1984;Bar et al, 2002 andSnow et al, 2004). Only two studies by Said et al (1984) and Snow et al (2004) fed different phosphorus levels throughout the second cycle and reported requirement of 0.3 and more than 2 g/kg of diet respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, fewer studies have investigated AP requirement of molted laying hens (Holder, 1981;Said et al, 1984;Bar et al, 2002 andSnow et al, 2004). Only two studies by Said et al (1984) and Snow et al (2004) fed different phosphorus levels throughout the second cycle and reported requirement of 0.3 and more than 2 g/kg of diet respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers suggested that evaluation of AP requirement of post molted laying hens is necessary because of lacking appropriate studies with this concept. Holder (1981) suggested that the available AP requirement in post-molt hens (28-wk study) was greater than 2.4 g/kg AP when calculated using NRC (1994) ingredient table values. Said et al (1984) investigated 2.1 and 3 g/kg AP levels (calculated using NRC, 1994 ingredient composition values) fed from 26 wk of age through an induced molt and during a 40-wk second cycle.…”
Section: Discussionmentioning
confidence: 99%
“…O desempenho de poedeiras tem sido prejudicado por baixos (SUMMERS et al, 1976;HOLDER, 1981;MILES et al, 1983;BAR e HURWITZ, 1984;JUNQUEIRA, 1988;e LEESON et al, 1993) ou altos níveis de fósforo dietético (MILES et al, 1983;JUNQUEIRA, 1988). Por outro lado, a qualidade da casca dos ovos também pode ser prejudicada por altos (OSTERHOUT, 1980;HARMS, 1982;MILES et al, 1983;SAID e SULLIVAN, 1985;JUNQUEIRA, 1988;SAKOMURA et al, 1993;e LEESON et al, 1993) ou baixos níveis de fósforo dietético (JUNQUEIRA, 1988;LEESON et al, 1993).…”
Section: Introductionunclassified
“…Por outro lado, a qualidade da casca dos ovos também pode ser prejudicada por altos (OSTERHOUT, 1980;HARMS, 1982;MILES et al, 1983;SAID e SULLIVAN, 1985;JUNQUEIRA, 1988;SAKOMURA et al, 1993;e LEESON et al, 1993) ou baixos níveis de fósforo dietético (JUNQUEIRA, 1988;LEESON et al, 1993). Contudo, há referências de melhoria da qualidade da casca dos ovos, quando se empregam baixos níveis de fósforo (HOLDER, 1981).…”
Section: Introductionunclassified
See 1 more Smart Citation